Citra Kawasan Manahan Kota Surakarta Sebagai Lokasi Stabilisasi PKL - Murtanti Jani Rahayu; Imam Buchori; Retno Widjajanti; Rufia Andisetyana Putri; Erma Fitria Rini (TATALOKA, 2020)
Stabilization as one of the street vendors arrangement type conducted by the government of Surakarta, that have great implications on the aesthetic style and form at some city parts. Some parts of Surakarta has changed a lot since the inauguration of the location, that is a public space, as a street vendors stabilization location in part of the area. Manahan area is one of the locations of street vendor stabilization that is considered successful. The presence of street vendors who have been arranged in the area Manahan able to attract visitors both weekand and weekdays, especially on holidays. This area is also more easily remembered by the visitors than other areas that there is no stabilization of street vendors. It means that this area has good and unique image quality that can be a memory for visitors. The purpose of this paper is to explore the image of street vendor Manahan stabilization area. Understanding the image of city area, principle that is used to assess the five basic elements of image formers include landmarks, path, edge, district and node. All five elements will be the componens in assessing the identity, identity and meaning that will shape the cognition of visitors so that it can be used as environmental orientation when someone is in a place. The introduction of Manahan stabilization area begins with stimulation done by graphic and visual technique before the interviews made a cognitive map in Stabilisasi PKL Manahan area and also made familiarity-favorability-semantic differensial assesment. This area has the potential of sustainability and good image compared to other stabilization locations, so that the managed street vendors can continue to grow and the location of the arrangement becomes an attractive area and supports the identity of the city of Surakarta as a merchant friendly city by staying a beautiful and friendly city for all the citizens and tourists who visit it.